(untitled) (ASEAN Engineering Journal, 2024)
Kaffir lime leaves (Citrus hystrix DC) are a natural antioxidant compound that can ward off free radicals due to the presence of flavonoid compounds. The flavonoids in this plant were extracted by extraction using a maceration method using 70% ethanol solvent with a soaking time of 24 hours. The ratio used between samples and solvent is 1:10. The microencapsulation process uses a drying method using an oven with maltodextrin coating combined with gelatin in the ratio (coating: kaffir lime leaf extract = 1: 2, 2: 2 and 4: 2) and dried using an oven at temperatures of 40℃, 45℃ and 50℃. Encapsulants with a variant ratio (coating: extract = 4:2) with a gelatin weight of 3 grams at a drying temperature of 50℃ showed the best results, namely 69.079%. Based on GC-MS testing, microencapsulated kaffir lime leaf extract contains compounds terpenoid, phenolic and fatty acid compounds. Antioxidant activity was tested using DPPH analysis and obtained an IC50 result of 48.5694 µg/ml. The morphological characteristics of the microencapsulation were tested using Scanning Electron Microscopy (SEM) analysis. The microencapsulation dissolution test showed that all samples disintegrated within 12 minutes. Overall, it can be concluded that microencapsulation made from maltodextrin and gelatin can encapsulate antioxidants in kaffir lime leaf extract well and dissolve easily at room temperature.